Fungsi Naratif Dongeng dalam Cerpen “Lu’lu’atu Ash-Shabāḥi” Karya Kamil Kailani - Khotimah, Husnul; Surur, Misbahus; Mustofa, Arif (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
In oral societies, the tradition of story telling has never truly disappeared. In modern times, folktales can be presented in the form of short stories. As a genre of prose, short stories possess their own distinct characteristics. Moreover, they often embed historical narratives, adventure tales, and heroic stories, which are typically presented through various engaging plot structures. One example of an Arabic short story rich in folktale elements is "Lu’lu’atu ash-Shabāḥi" by Kamil Kailani. This study aims to uncover the narrative functions in the short story to illustrate the pattern of the protagonist’s journey, using Vladimir Propp’s narrative approach. This research employs a Descriptive Qualitative Method. Data collection was carried out through reading, translating, and note-taking techniques. Data analysis was conducted using Miles and Huberman’s method, which includes identifying findings and marking them according to Propp’s narrative functions. The findings are then described by linking the story’s context or plot to the theoretical framework. The results show that 16 out of the 31 narrative functions proposed by Vladimir Propp are present in the story. These 16 functions include Initial Situation (α), Absentation (β), Interdiction (γ), Violation (δ), Mediation (B), Counter-Action (C), Trickery (η), Complicity (θ), Villany (A), Departure (↑), Guidance (G), Victory (J), Solution (N), Difficult Task (M), Return (K), and Recognition (R).Keywords - Arabic Short Story, Narrative Functions, Narrative Structuralism, Vladimir Propp.